Complex training of language learning advisor: Experience linked to the self-access center Support Base for Autonomous Learning (Research, Society and Development, 2021)
Language learning advising is an activity offered at university self-access centers. One of its roles is to support the learning process of foreign language students with regard to autonomy and motivation. The research “Formation of a language learning advising with an entrepreneurial bias and the motivational process of a self-access center team” has among its objectives to propose ways to form language learning advisors who can work in self-access centers, as well as in the job market. In this action research carried out under the complexity approach, we investigate how this phenomenon unfolds. Some of the results obtained show that: (i) the steps take place in an interconnected way: one learns about the language learning advising activity by exercising the role of advisor in guided practices with students who are advisees, by discussing the attitudes that are taken and the support readings on the theme of language learning advising, motivation and entrepreneurship; (ii) the configuration of the research group is that of a dynamic support network with advisors who are also researchers that present diverse linguistic competence as users of the target foreign language and who attend or have already attended the self-access center in which this study is linked by having participated in it its managing staff as a volunteers or as a scholarship holder who helps to organize the space and activities offered on it.